2008
DOI: 10.1590/s1676-06032008000100019
|View full text |Cite
|
Sign up to set email alerts
|

Cladóceros fitófilos (Crustacea, Branchiopoda) do Parque Nacional das Emas, estado de Goiás

Abstract: Este trabalho apresenta um inventário preliminar de cladóceros fitófilos do Parque Nacional das Emas. Onze amostras qualitativas foram coletados de diferentes ambientes (lagoa, vereda e campo úmido), no período de 2000 a 2006. Foram identificadas 18 espécies, pertencentes a famílias tipicamente não planctônicas, sendo Chydoridae a mais especiosa. Todas elas representam o primeiro registro para a região sudoeste de Goiás.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 17 publications
1
20
0
2
Order By: Relevance
“…The dominance of the Chydoridae family was also reported by other researchers (Elmoor-Loureiro, 2007b;Elmoor-Loureiro and Mendonça-Galvão, 2008;Maia-Barbosa et al, 2008;Sousa and Elmoor-Loureiro, 2008;Castilho-Noll et al, 2010;Soares and Elmoor-Loureiro, 2011) (Table 4). This fact may be related to the peculiar characteristics of organisms in this family that have a thicker shell, spines and appendages specialized in grasping substrates, allowing greater mobility and success in the littoral lake areas.…”
Section: Discussionsupporting
confidence: 82%
“…The dominance of the Chydoridae family was also reported by other researchers (Elmoor-Loureiro, 2007b;Elmoor-Loureiro and Mendonça-Galvão, 2008;Maia-Barbosa et al, 2008;Sousa and Elmoor-Loureiro, 2008;Castilho-Noll et al, 2010;Soares and Elmoor-Loureiro, 2011) (Table 4). This fact may be related to the peculiar characteristics of organisms in this family that have a thicker shell, spines and appendages specialized in grasping substrates, allowing greater mobility and success in the littoral lake areas.…”
Section: Discussionsupporting
confidence: 82%
“…In Brazil, approximately 140 species have already been recorded (Elmoor-Loureiro, 1997;Paggi and Rocha, 1999;Santos-Wisniewski, et al, 2001;Lopes et al, 2006;Sousa et al, 2008;Lansac-Tôha et al, 2009), although a large area of the territory, with various types of biotopes, has not yet been studied.…”
Section: Methodsmentioning
confidence: 99%
“…In another study in shallow wetlands in the Brazilian Cerrado, Sousa and Elmoor-Loureiro (2008) found 11 species in the richest site and four in the poorest site in an inventory of Cladocera fauna conducted in the Emas National Park, also in Goia´s state. Their results are quite similar to the ones reported by this study the BNP and FIC (Tables 4 and 5), and it is noticeable that the number of species is very similar.…”
Section: Discussionmentioning
confidence: 92%
“…In case of Cladocera, which the most species live in association with aquatic macrophytes (Forro´et al, 2008), the information is only preliminary (Elmoor-Loureiro, 2007;Sousa and Elmoor-Loureiro, 2008). These studies presented the species richness; however, there was no attempt to assess the sampling effort because no systematized methods was used for data collection.…”
Section: Introductionmentioning
confidence: 99%